(3GdeYHO TQM GdeLQOs - (3Sdje Hf CjhH Hf Sdje GdQGRqj, CHh GdaJM,J (B447 (3g` s
(3ChdgG (B:s
(3jHOC cJGH GdQLYI s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B243s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1593s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs